APPLICATION FEATURES OF ELECTRONIC TEACHING MATERIALS IN PROFESSIONAL TRAINING OF SPECIALISTS IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - Julia Barkova (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article considers the peculiarities of the use of electronic learning tools in the process of training future specialists in physical education and sports. An analysis of the scientific literature on the use of electronic tools in the educational process in higher education is conducted. The experience of using e-learning tools in the process of training specialists in physical education and sports at Zaporizhia National University is generalized. A classification has been formed and four groups of e-learning tools have been substantiated for the training of future specialists in physical education and sports. The first group includes an electronic textbook. It is established that its educational functionality is higher than that of paper. The second group included quasi-professional learning tools using Google Wave, Google Groups, Zoom, FreeConferenceCall, Google Meet, Kahoot and QUIZIZZ, as well as LearningApps tools, which gave students the opportunity to create their own interactive exercises and learning games. The third group included multimedia teaching tools for creating presentations using Prezi, online application for animated video presentations PowToon, video editors Windows Movie Maker and VSDC Free Video Editor, visualization tools using online graphics services Google Developers, Easel.ly, Piktochart, Infogr.am, graphic editors Adobe Photoshop, The GIMP, Paint.net, PhotoInstrument, as well as tools for reproducing educational virtual reality using mobile VR-helmets OCULUS GO, MIRAGE SOLO, GEAR VR. The fourth group of e-learning tools in the training of future specialists in physical culture and sports included e-learning tools and its components, in particular, software and hardware Moodle, which allows you to develop exercises and tests to consolidate theoretical material and generalize knowledge of specialists in physical culture and sports. Scientific and methodological substantiation and recommendations on the use of electronic learning tools in the process of training specialists in physical culture and sports are provided.